High-Throughput and Accurate Determination of Transgene Copy Number and Zygosity in Transgenic Maize: From DNA Extraction to Data Analysis - Liu, Fang; Cheng, Jinkui; Liu, Xuhua; Wang, Xi-Qing (International journal of molecular sciences, 2021)
It is vital to develop high-throughput methods to determine transgene copy numbers initially and zygosity during subsequent breeding. In this study, the target sequence of the previously reported endogenous reference gene hmg was analyzed using 633 maize inbred lines, and two SNPs were observed. These SNPs significantly increased the PCR efficiency, while the newly developed hmg gene assay (hmg-taq-F2/R2) excluding these SNPs reduced the efficiency into normal ranges. The TaqMan amplification efficiency of bar and hmg with newly developed primers was calculated as 0.993 and 1.000, respectively. The inter-assay coefficient of variation (CV) values for the bar and hmg genes varied from 1.18 to 2.94%. The copy numbers of the transgene bar using new TaqMan assays were identical to those using dPCR. Significantly, the precision of one repetition reached 96.7% of that of three repetitions of single-copy plants analyzed by simple random sampling, and the actual accuracy reached 95.8%, confirmed by T1 and T2 progeny. With the high-throughput DNA extraction and automated data analysis procedures developed in this study, nearly 2700 samples could be analyzed within eight hours by two persons. The combined results suggested that the new hmg gene assay developed here could be a universal maize reference gene system, and the new assay has high throughput and high accuracy for large-scale screening of maize varieties around the world.